Ammonia-oxidizing bacteria are more responsive than archaea to nitrogen source in an agricultural soil. (May 2016) - Ouyang, Yang; Norton, Jeanette M.; Stark, John M.; Reeve, Jennifer R.; Habteselassie, Mussie Y.
Abstract: In the majority of agricultural soils, ammonium (NH4 + ) is rapidly converted to nitrate (NO3 − ) in the biological ammonia and nitrite oxidation processes known as nitrification. The often rate-limiting step of ammonia oxidation to nitrite is mediated by ammonia oxidizing bacteria (AOB) and ammonia oxidizing archaea (AOA). The response of AOA and AOB communities to organic and conventional nitrogen (N) fertilizers, and their relative contributions to the nitrification process were examined for an agricultural silage corn system using a randomized block design with 4 N treatments: control (no additional N), ammonium sulfate (AS) fertilizer at 100 and 200 kg N ha −1, and steer-waste compost (200 kg total N ha −1 ) over four seasons. DNA was extracted from the soil, and real-time PCR and 454-pyrosequencing were used to evaluate the quantity and diversity of the amoA gene which encodes subunit A of ammonia monooxygenase. Soil pH, nitrate pools, and nitrification potentials were influenced by ammonium and organic fertilizers after the first fertilization, while changes in AOB abundance and community structure were not apparent until after the second fertilization or later. The abundance of AOA was always greater than AOB but was unaffected by N treatments. In contrast, AOB abundance and community structure were changed significantly by ammonium fertilizers. Specific inhibitors of nitrification were used to evaluate the relative contribution of AOA and AOB to nitrification. We found that AOB dominantly contributed to potential nitrification activity determined at 1 mM ammonium in soil slurries and nitrification potential activity was higher in soils treated with ammonium fertilizers relative to control soils. However, AOA dominated gross nitrification activity in moist soils. Our result suggests that AOB activity and community are more responsive to ammonium fertilizers than AOA, but that in situ nitrification rate is controlled by ammonium availability in this agricultural soil. Understanding this response of AOA and AOB to N fertilizers may contribute to improving strategies for the management of nitrate production in agricultural soils. Highlights: Quantity and community of AOB are more responsive to ammonium fertilizers than AOA. AOB dominantly contributed to nitrification in soil slurries at 1 mM ammonium. AOA dominated gross nitrification activity in moist soils at ambient ammonium. Approaches to control nitrification should focus on AOB shortly after fertilization.